(untitled) (TEMU ILMIAH NASIONAL PERSAGI, 2023)
The World Health Organization (WHO) recommends babies to get exclusive breastfeeding for 0-6 months so that the baby's growth and development is optimal. In Indonesia, according to data from the Ministry of Health in 2017, infants who received breast milk for 0-6 months only reached 35.73 percent, an increase from the 2016 achievement of 29.5 percent. However, the achievement of exclusive breastfeeding is still below the national target in 2017 which is 44 percent. The purpose of this study was to increase knowledge related to exclusive breastfeeding strategies, how to overcome problems when breastfeeding and lactation management. The research method was carried out with One-Group Pre Test Post Test Design with a sample of 31 pregnant women in the third trimester. The results showed that there were differences in the average knowledge score of pregnant women and differences in attitudes of pregnant women in the third trimester before and after being given an intervention using the Booklet Series Literacy 1 (Breastmilk for the baby) has increased.